Cost-utility analysis of triple therapy with telaprevir in treatment-naïve hepatitis C patients - Blanca Gros; María Buti; Itziar Oyagüez; Raúl J Andrade; Miguel A. Serra; Juan Turnes; Miguel A. Casado (Farmacia Hospitalaria)
Introduction: The prevalence of Hepatitis C (HCV) in Spain is 2,5%, with a high morbimortality rate. Triple therapy based on telaprevir plus peginterferon/ribavirin ([T/PR]) has demonstrated to be an effective approach in treatment-naïve G1-HCV patients. This analysis evaluated, through a Markov model, the incremental cost-effectiveness ratio of triple therapy compared to peginterferon/ ribavirin ([PR]) alone in naïve patients depending on fibrosis stage, from the Spanish Healthcare Authorities perspective. Methods: Efficacy results and adverse events incidence were based on the combined results of ADVANCE and OPTIMIZE studies. Adverse events and disease-related costs (€, 2014) were built up from panel expert opinion except from transplant and post-transplant costs, taken from published data. Drug costs were obtained from national databases and adjusted for the mandatory deduction. Outcomes and costs were both discounted at 3%/year. Results: The analysis shows higher costs and improved outcomes associated with [TR/PR] relative to [PR] alone, resulting in an incremental cost-effectiveness ratio (ICER) of €18,288/ QALY for all the cohort, €14,152QALY for moderate fibrosis, €11,364QALY for bridging fibrosis, €15,929/QALY for cirrhosis. Over a lifetime period, the use of [T/PR] could avoid 12 cirrhosis and 4 liver transplants per 1,000 patients compared to [PR] alone. The probabilistic analysis, following 10,000 Montecarlo simulations, demonstrated the probability of an ICER below a €30,000/QALY gained threshold of 69%. At a willingness- to-pay of €30,000/QALY, [T/PR] could be considered as an efficient option compared with [PR] alone for treatment-naïve genotype 1 HCV patients, over a lifetime horizon